Efeito do preparo do solo e resíduo da colheita de cana-de-açúcar sobre a emissão de CO2 - Moitinho, Mara Regina [UNESP] (2013)
The soil is one of the main C pools in terrestrial ecosystem, capable of storing significant C amounts. Therefore, understanding the factors that contribute to the loss of CO2 from agricultural soils is critical to determine strategies reducing emissions of this gas and help mitigate the greenhouse effect. The purpose of this study was to investigate the effect of soil tillage and sugarcane trash on CO2 emissions, temperature and soil moisture during sugarcane (re)planting, over a study period of 15 days. The following managements were evaluated: no-tillage with crop residues left on the soil surface (NTR); without tillage and without residue (NTNR) and tillage with no residue (TNR). The average soil CO2 emission (FCO2) was lowest in NTR (2.16 µmol m-2 s-1), compared to the managements NTNR (2.90 µmol m-2 s-1) and TNR (3.22 µmol m-2 s-1), indicating that the higher moisture and lower soil temperature variations observed in NTR were responsible for this decrease. During the study period, the lowest daily average FCO2 was recorded in NTR (1.28 µmol m-2 s-1), and the highest in TNR (6.08 µmol m-2 s-1), after rainfall. A loss of soil CO2 was lowest from the management NTR (367 kg ha-1 of CO2-C) and differing significantly (p<0.05) from the managements NTNR (502 kg ha-1 of CO2-C) and TNR (535 kg ha-1 of CO2-C). Soil moisture was the variable that differed most managements and was positively correlated (r = 0.55, p<0.05) with the temporal variations of CO2 emission from NTR and TNR. In addition, the soil temperature differed (p<0.05) only in management NTR (24 °C) compared to NTNR (26 °C) and TNR (26.5 °C), suggesting that under the conditions of this study, sugarcane trash left on the surface induced an average rise in the of soil temperature of 2 ºC.